2016
DOI: 10.1123/jsr.2014-0289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salted Ice Bags on Surface and Intramuscular Tissue Cooling and Rewarming Rates

Abstract: Wetted- and salted-cubed-ice bags were equally effective at decreasing intramuscular temperature at 2 cm subadipose. Clinical practicality may favor salted-ice bags over wetted-ice bags.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…However, skin temperature is highly variable and is further influenced by the presence of a barrier and the addition of external compression. Correlations in this study as well as previous studies 12,19,27 have demonstrated no correlation between skin and muscle temperatures, indicating that skin temperatures cannot be utilized to approximate muscle temperature decreases.…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…However, skin temperature is highly variable and is further influenced by the presence of a barrier and the addition of external compression. Correlations in this study as well as previous studies 12,19,27 have demonstrated no correlation between skin and muscle temperatures, indicating that skin temperatures cannot be utilized to approximate muscle temperature decreases.…”
Section: Discussioncontrasting
confidence: 39%
“…11 Another study has found salted ice bags (2000mL cubed ice + ½ tbsp salt) to be equivalent to wetted ice at decreasing intramuscular temperature. 12 The PP-ice in our study decreased intramuscular temperature (2cm depth) 4.8°C. Previous research has found a wet ice (parameters not provided) wrapped with 45mmHg of elastic compression to decrease 4.46C (2cm depth) during a 30-minute treatment.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations